Decide + Be Ready: A Contraceptive Decision-Making Mobile Application for Servicewomen. Issue 11 (19th May 2021) - Witkop, Catherine T; Torre, Dario M; Maggio, Lauren A
ABSTRACT: Women in the military have a high rate of unintended pregnancies, which is an issue both personally and with respect to the warfighting mission. One strategy to help servicewomen achieve family planning goals includes increasing education about and access to contraception. Research suggests that preference-sensitive decisions about contraceptives benefit from shared decision-making, and decision aids have been shown to facilitate this patient-centered approach. In this article, we describe the process by which we enhanced an existing evidence-based tool to meet the needs of military servicewomen and created Decide + Be Ready, a contraceptive decision-making mobile application. After extensive research into challenges faced by servicewomen with respect to contraceptive knowledge and access, we developed content for the decision aid and determined that a mobile app format would provide the privacy and convenience needed. Our team developed a prototype that, in collaboration with the Defense Health Agency Connected Health Branch, was tested with servicewomen and providers. User feedback shaped the final version, which can be accessed free from the App Store and Google Play. Early implementation has demonstrated patient and provider satisfaction. Obstacles to full implementation of Decide + Be Ready remain within the Military Health System. We lay out a roadmap for dissemination, implementation, and evaluation and explore the applications of the decision aid for health professions education in the realm of shared decision-making. Finally, we recommend consideration of decision aids for other health care decisions as a way to achieve patient-centered care, improve health outcomes, and potentially reduce costs.